2023
DOI: 10.29333/ejmste/12845
|View full text |Cite
|
Sign up to set email alerts
|

Technological pedagogical content knowledge self-efficacy of pre-service science and mathematics teachers: A comparative study between two Zambian universities

Abstract: Pre-service science and mathematics teachers’ beliefs and attitudes concerning technology integration significantly influence how confident they are to integrate technology into their teaching. This study is a comparative examination of the technological pedagogical content knowledge (TPACK) self-efficacy of 202 pre-service science and mathematics teachers enrolled at two Zambian universities. It also investigated the influence of selected demographic variables on the TPACK self-efficacy of pre-service science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 41 publications
0
6
0
2
Order By: Relevance
“…Domain yang keempat yaitu kemampuan berpikir inventif yang merupakan keterampilan kognitif yang sangat penting dalam membuat tugas-tugas tertentu lebih mudah dan sederhana khusunya dengan bantuan teknologi. Dalam studi ini, keterampilan berpikir inventif mengacu pada keterampilan yang dibutuhkan siswa yaitu fleksibilitas, pengaturan diri, dan rasa ingin tahu (Ajayi, 2018;Bwalya & Rutegwa, 2023;Suwono et al, 2022). Keterampilan-keterampilan tersebut merupakan unsur nilai yang dimasukkan dalam kerangka pengembangan instrumen ini karena sejalan dengan aspirasi pendidikan nasional untuk menghasilkan individu yang tidak hanya berpengetahuan dan juga terampil tetapi mereka juga memiliki sopan santun dan nilainilai yang baik dalam mengatur dirinya.…”
Section: Hasil Dan Pembahasanunclassified
“…Domain yang keempat yaitu kemampuan berpikir inventif yang merupakan keterampilan kognitif yang sangat penting dalam membuat tugas-tugas tertentu lebih mudah dan sederhana khusunya dengan bantuan teknologi. Dalam studi ini, keterampilan berpikir inventif mengacu pada keterampilan yang dibutuhkan siswa yaitu fleksibilitas, pengaturan diri, dan rasa ingin tahu (Ajayi, 2018;Bwalya & Rutegwa, 2023;Suwono et al, 2022). Keterampilan-keterampilan tersebut merupakan unsur nilai yang dimasukkan dalam kerangka pengembangan instrumen ini karena sejalan dengan aspirasi pendidikan nasional untuk menghasilkan individu yang tidak hanya berpengetahuan dan juga terampil tetapi mereka juga memiliki sopan santun dan nilainilai yang baik dalam mengatur dirinya.…”
Section: Hasil Dan Pembahasanunclassified
“…Based on the importance of mathematics teachers' knowledge, and the significance of training them to be effective teachers in mathematics learning environments, research studies were conducted on conceptual understanding and pedagogical knowledge of mathematics teachers, as separate variables, around the world and in Jordan (Al-Barakat et al, 2022a;Al-Hassan et al, 2012;Al-Tarawneh, 2019;Bwalya & Rutegwa, 2023;Fraihat et al, 2022;Khasawneh et al, 2023;Mapulanga et al, 2022;Meier, 2021;Shaqar, 2020).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…In the same context, numerus researchers (Mapulanga et al, 2022;Meier, 2021;Ponte, 2001) raised several issues facing the mathematics teacher in planning and practice in the classroom; These include selecting and designing investigative situations, adapting and adopting curriculum vocabulary, selecting teaching and assessment tasks, formulating objectives, and defining the form of procedures that fit the characteristics of students and their previous experiences. Moreover, some studies (Alali & Al-Barakat, 2022;Bwalya & Rutegwa, 2023;Ponte, 2001) identified a set of characteristics of the learning tasks in the classroom, the most prominent of which are that they are rich in concepts, unfamiliar, require justification, and stimulate solving the issue in various life contexts. In addition, it was emphasized that professional development programs can be achieved through courses, projects, exchange of experiences, readings, reflection on the experiences of others, and others, and that they must balance theory and practice (Bwalya & Rutegwa, 2023;Mapulanga et al, 2022;Meier, 2021;Ponte, 2001).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations